Fetoscopy for meningomyelocele repair: past, present and future - Nicole Silva Bevilacqua; Denise Araujo Lapa Pedreira (Einstein (São Paulo))
ABSTRACT Meningomyelocele is a malformation with high prevalence, and one of its main comorbidities is Arnold-Chiari malformation type II. The intrauterine repair of this defect has been studied to reduce the progressive spinal cord damage during gestation. The purpose of the present review was to describe the evolution of fetal surgery for meningomyelocele repair. Searches on PubMed database were conducted including articles published in the last 10 years. Twenty-seven articles were selected, 16 experimental studies and 11 studies in humans. A recent study demonstrated that the fetal correction results in better prognosis of neurological and psychomotor development, but open surgery, which has being used widely, has considerable maternal risks. Studies in animal and human models show that the endoscopic approach is feasible and leads to lower maternal morbidity rates. Two endoscopic techniques are currently under assessment - one in Germany and another in Brazil, and we believe that the endoscopic approach will be the future technique for prenatal repair of this defect.